168 Traumatic brain injury and sociodemographic factors: a review. Issue 9 (12th August 2022) - Vidot, Micha; Wu, Kit; Mitchell, James; Nitkunan, Arani; Carr, Georgina
Abstract : Background: To improve equity of service, in line with the aspirations of public policy across the UK, it is imperative that we understand how sociodemographic factors affect the management and care of traumatic brain injury (TBI). Aims: To describe the relationship between sociodemographic factors and the epidemiology, clinical factors, diagnosis, treatment, patient experience and outcomes for people with TBI. Methods: We conducted a focused review of published literature from 2000 to 2021 discussing TBI and each of the patient protected characteristics, as outlined in the Equality Act 2010, with additional factors such as education, employment and socioeconomic status also included. Results: There is some evidence investigating TBI in regards to age, race, sex and gender. There are gaps in research exploring the relationship between TBI and disability, gender reassignment, marriage and civil partnership, pregnancy, religion, sexual orientation, geographical variation, socioeconomic status, settlement status, education and employment. Discussion: Whilst there is some data on the incidence of TBI, further research is required to examine the association of certain sociodemographic protected characteristics to aid improvements in patient experience and outcomes.